Attentional set to safety recruits the ventral medial prefrontal cortex. Issue 1 (December 2018) - Yao, Shuxia; Qi, Song; Kendrick, Keith; Mobbs, Dean
Abstract Early detection of danger is highly adaptive, yet fast orientation towards safety is also key to survival. This study aimed to explore how human brain searches for safety by manipulating subjects' attentional set. Subjects were asked to judge random dots motion (RDM) direction and could be shocked for incorrect responses (RDM trials) while keeping alert in detecting shock probability cues (cue detection trials). Relative to safe condition, where attention was set to search cues associated with no shock, incorrect responses to 'dangerous+' cues would increase and correct responses to 'dangerous−' cues would decrease shock probability. In RDM trials, relative to the 'dangerous+', the safe and 'dangerous−' attentional set induced stronger activation in the ventral medial prefrontal cortex (vmPFC), a core region involved in flexible threat assessment and safety signalling. In cue detection trials, shorter response times and greater accuracy were observed for 'dangerous+' than 'dangerous−' and safe cues. At neural level 'dangerous+' cues induced stronger activity in the frontoparietal attention network than safe cues. Overall, our findings demonstrate that attentional set for searching safety recruits the vmPFC, while detection of threat-related cues elicits activity in the frontoparietal attention network, suggesting new roles for these regions in human defensive survival circuitry.